HCMV UL97 phosphotransferase gene mutations may be associated with antiviral resistance in immunocompromised patients in Bel?m, PA, Northern Brazil - Silva, Dorot?a de F?tima Lobato da (Sociedade Brasileira de Medicina Tropica, 2018)
Introduction: Human cytomegalovirus is one of the causes of opportunist infections in immunocompromised patients, and is triggered by factors such as state of viral latency, weakened immune responses, and development of antiviral resistance to ganciclovir, the only drug offered by the public health system in Brazil to treat the infection. The goal of this study was to identify mutations that may be associated with antiviral resistance in immunocompromised patients. Methods: Molecular analysis was performed in 82 blood samples and subjected to genomic DNA extraction by a silica-based method. Three sequences of the HCMV UL97 gene, which encodes a phosphotransferase protein required for activation of ganciclovir, were amplified by polymerase chain reaction. Pyrosequencing methods were applied to one external 2096-bp segment DNA and two internal sequences between nucleotides 1087 to 1828 to detect mutations in this gene. Results: Approximately 10% of sequences contained mutations between nucleotides 377 and 594, in conserved regions of the UL97 gene, leading to amino acid changes. Eleven coding mutations were identified, including changes leading to amino acid substitutions, E596K and S604F, which were observed in 100% of samples and are described for the first time in Brazil. In addition, one mutation (A594V) that is associated with ganciclovir resistance was detected in a kidney transplant patient. Conclusions: Further studies to detect mutations associated with HCMV resistance to antiviral drugs are required to demonstrate the need to increase the variety and availability of drugs used to treat viral infections in the public health care system in Brazil